The bisphosphonate zoledronic acid regulates key angiogenesis-related genes in primary human gingival fibroblasts. (March 2016) - Ohlrich, E.J.; Coates, D.E.; Cullinan, M.P.; Milne, T.J.; Zafar, S.; Zhao, Y.; Duncan, W.D.; Seymour, G.J.
Highlights: Zoledronic acid (ZA) affects gene expression in human gingival fibroblasts. Fibroblasts respond to ZA by upregulating the proangiogenic genes VEGF and BMP2. RHOB gene regulation is consistent with effects on the mevalonate pathway. CCL2, IL6, and CD55 regulation links ZA to the suppression of the inflammation. Abstract: Background: Osteonecrosis of the jaws is recognised as a serious complication for patients receiving bisphosphonates. The anti-angiogenic effects of bisphosphonates have been implicated in the pathogenesis of bisphosphonate-related osteonecrosis of the jaw (BRONJ). The purpose of this study was to determine the effects of zoledronic acid on cultured human gingival fibroblasts in relation to the modulation of genes associated with angiogenic regulation. Methods: Primary cultures of fibroblasts were developed from gingival tissues excised during crown-lengthening surgery from three patients. Cells were cultured with and without 30 μM zoledronic acid for 6, 12 and 24 h and cellular proliferation and migration investigated using CellTiter-Blue and scratch wound assays, respectively. Gene expression was determined using semi-quantitative PCR array technology that allowed the analysis of 84 pathway-focused genes known to be important in the regulation of angiogenesis. Results: Zoledronic acid increased the proliferation of the gingival fibroblasts in a dose dependent manner with 12 and 24 h of exposure. Scratch wounding of the human gingival fibroblasts and treatment with increasing doses and time exposure to zoledronic acid (ZA) inhibited their migration. Statistically significant increases in gene expression were found for RHOB, VEGFA, CD55 and BMP2 ( p  ≤ 0.05) in response to 30 μM zoledronic acid. CCL2 and IL6 genes were significantly downregulated ( p  ≤ 0.05). Conclusions: The regulation of the prenylated protein RHOB in this study was consistent with the known effects of zoledronic acid on the mevalonate pathway. The down regulation of CCL2 and IL6 and the upregulation of CD55 may be associated with suppression of inflammation. An increase in VEGFA and BMP2 gene expression suggests that fibroblasts respond to zoledronic acid by producing a proangiogenic environment.